2005
DOI: 10.1007/s11010-005-2989-0
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protective effect of octylguanidine against the damage induced by ischemia reperfusion in rat heart

Abstract: This study shows that the hydrophobic cation octylguanidine protects against myocardial damage induced by ischemia-reperfusion. The protective effect of the amine was analyzed after 5 min of coronary occlusion followed by 5 min reperfusion in rat hearts. ECG tracings from rats treated with an i.v., injection of 5 mg/kg of octylguanidine showed a total absence of post-reperfusion arrhythmias, conversely to what was observed in untreated rats. The histological images showed that myocardium fibers from treated ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…To this regard, we demonstrated previously that OG protects mitochondria from permeability transition as induced by carboxyatractyloside, through blocking ANT [26]. We also showed that OG maintains the myocardium in a good shape, protecting it against the damage induced by ischemia/reperfusion [27]. The results in this work indicate that OG inhibited reperfusion arrhythmias and reduced the incidence of ventricular tachycardia in hearts isolated from hyperthyroid rats.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…To this regard, we demonstrated previously that OG protects mitochondria from permeability transition as induced by carboxyatractyloside, through blocking ANT [26]. We also showed that OG maintains the myocardium in a good shape, protecting it against the damage induced by ischemia/reperfusion [27]. The results in this work indicate that OG inhibited reperfusion arrhythmias and reduced the incidence of ventricular tachycardia in hearts isolated from hyperthyroid rats.…”
Section: Discussionsupporting
confidence: 67%
“…The mass and purity of the reagent was assessed by Dr. Roberto Arreguín from the Instituto de Química, UNAM, by using two methods, mass spectrometry and high performance liquid chromatography, indicating that the purity attained was 90% and 98%, respectively, with a molecular weight of 171 Da, which agrees closely with its molecular composition. In agreement with previous work [27], the amine was administered at a dose of 5 mg/kg body weight, injected through the femoral vein 10 min before starting the ischemic period.…”
Section: Octylguanidine Administrationmentioning
confidence: 80%
See 2 more Smart Citations
“…4), have been used as protectors against reperfusion injury [55,56]. Other examples are sanglifehrin A [57] and, more recently, NIM811 [58] and octylguanidine [59].…”
Section: I6 Mitochondrial Calcium Uptake Inhibitorsmentioning
confidence: 99%